10 Little Fairies : A Tale Of Friends You Can Count On - Melanie Joyce (China Igloo Books L:td, 2016)
Ten Little fairies are going to be late for Fairy School! Will they be able to make it there in time, or even at all Join the fluttering fairies on their journey and find out whether the trip is as simple as it seems. With magic, doors, enchanted trees and wonderful characters, this charming storybook is full of fairy fun.
Keywords: Math Stories -- Math Stories